The reading of Nafi‘ al-Madani in the Central Maghreb (Algeria) between historical perspective and future outlook - zeghad, lazhar (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : Quranic readings are the most important sciences of the Holy Qur'an, for their interest in correcting the crookedness of the tongue when chanting, as well as transferring how to pronounce them from the Prophet's presence, so he became famous from the ten readers, each of them read in the states of the Islamic State, and his reading was famous so that he could not read only by them, and the city was singled out for its largest reader Nafi Al-Madani, whose reading flew in every direction, so Imam Malik praised it by saying: "Reading Nafi' Sunnah", and the Arab Maghreb was famous for reading Nafi' from among the ten reciters, so the aim of this research was to stand On the history of the entry of Nafi's reading into Algeria, as well as the efforts of scholars to preserve it, with a look at the reality of reading, and the challenges it faced, between reality and the future.